2023
DOI: 10.3390/su15118540
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity as an Outstanding Universal Value for Integrated Management of Natural and Cultural Heritage

Kiriaki M. Keramitsoglou,
Panagiotis Koudoumakis,
Sofia Akrivopoulou
et al.

Abstract: UNESCO’s World Heritage Centre has set ten criteria for assessing Outstanding Universal Values (OUVs) for the inscription of properties on the World Heritage List. Recognising the growing challenge for heritage conservation and the need for professionals to work within systemic, holistic, and integrated frameworks in managing cultural heritage and using biodiversity as an OUV, this paper investigates how the intangible and tangible cultural and natural heritage of the Region of East Macedonia and Thrace, Greec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Exploring delicate, impeccable, and largely unaltered natural places is known as ecotourism [1][2][3][4][5][8][9][10][11][12]. It is a low-impact, frequently small-scale substitute for traditional commercial mass tourism that is common in megacities and urban areas where people travel around for sightseeing [17].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Exploring delicate, impeccable, and largely unaltered natural places is known as ecotourism [1][2][3][4][5][8][9][10][11][12]. It is a low-impact, frequently small-scale substitute for traditional commercial mass tourism that is common in megacities and urban areas where people travel around for sightseeing [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These wetlands can absorb and store large volumes of floodwater, which can help to lessen the frequency and severity of floods in the community (campus). A wetland can normally hold one million gallons of water, or around three acres, submerged three feet under [8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]32]. When hurricanes or tropical storms hit land, coastal wetlands buffer land from storm surges [30][31][32].…”
Section: What Is Restoration?mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, cultural heritage management activity provides some protection for natural heritage compared to other highly disturbed human ecosystems. This allows the growth of vegetation with natural or semi-natural features in these areas, with species and plant communities of conservation interest [28,30,31]. In some instances, it has been observed that the latter could even quadruple in number compared to other humanmodified contexts, where they are often threatened [29,[32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%